2013
DOI: 10.6061/clinics/2013(05)11
|View full text |Cite
|
Sign up to set email alerts
|

Oscillation mechanics of the respiratory system in never-smoking patients with silicosis: pathophysiological study and evaluation of diagnostic accuracy

Abstract: OBJECTIVES:Silicosis is a chronic and incurable occupational disease that can progress even after the cessation of exposure. Recent studies suggest that the forced oscillation technique may help to clarify the changes in lung mechanics resulting from silicosis as well as the detection of these changes. We investigated the effects of airway obstruction in silicosis on respiratory impedance and evaluated the diagnostic efficacy of the forced oscillation technique in these patients.METHODS:Spirometry was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 39 publications
6
15
0
1
Order By: Relevance
“…Other authors, investigating early changes in sarcoidosis, found results similar to our findings [28]. These results are also consistent with those observed in systemic sclerosis [23], silicosis [29] and smoking [77]. In subjects with coal mining-related pneumoconiosis, a pattern of reticular nodulation on the chest radiograph was reported, representing the initial stage of dust deposition in the lung.…”
Section: Discussionsupporting
confidence: 92%
“…Other authors, investigating early changes in sarcoidosis, found results similar to our findings [28]. These results are also consistent with those observed in systemic sclerosis [23], silicosis [29] and smoking [77]. In subjects with coal mining-related pneumoconiosis, a pattern of reticular nodulation on the chest radiograph was reported, representing the initial stage of dust deposition in the lung.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with other studies, 21,22 patients with silicosis showed changes in both reactive and resistive properties of the respiratory system. Silicosis is characterized by airway impairment owing to its distortion and compression by the silicotic nodules and the involvement of the lung parenchyma owing to the conglomerate masses and scar-related emphysema.…”
Section: Full Paper: Pulmonary Densitometry and Forced Oscillation Tesupporting
confidence: 80%
“…Thus, the extensive replacement of the pulmonary parenchyma by fibrous tissue in patients with silicosis can contribute to changes in elasticity, which in turn can cause an imbalance in the respiratory system's time constants and increase the heterogeneity of the system. 22 In this study, a reduced dynamic compliance of the respiratory system was associated with larger size and higher weight of nonaerated compartment. Dynamic compliance of the respiratory system includes the compliances of the lung and bronchial walls, the chest wall and thoracic gas compression.…”
Section: Full Paper: Pulmonary Densitometry and Forced Oscillation Tementioning
confidence: 88%
See 2 more Smart Citations